Molecular Mechanisms of MYCN Dysregulation in Cancers - Liu, Ruochen; Shi, Pengfei; Wang, Zhongze; Yuan, Chaoyu; Cui, Hongjuan (Frontiers in Oncology, 2021)
MYCN, a member of MYC proto-oncogene family, encodes a basic helix-loop-helix transcription factor N-MYC. Abnormal expression of N-MYC is correlated with high-risk cancers and poor prognosis. Initially identified as an amplified oncogene in neuroblastoma in 1983, the oncogenic effect of N-MYC is expanded to multiple neuronal and nonneuronal tumors. Direct targeting N-MYC remains challenge due to its “undruggable” features. Therefore, alternative therapeutic approaches for targeting MYCN-driven tumors have been focused on the disruption of transcription, translation, protein stability as well as synthetic lethality of MYCN. In this review, we summarize the latest advances in understanding the molecular mechanisms of MYCN dysregulation in cancers.